A Concept Analysis of Empathy - Firth, Hannah (2011)
This concept analysis is based on Walker and Avant’s (1995) model. Data was collected from a number of search engines in July 2010 and an inclusion and exclusion criteria was added. A final search was completed in January 2011 to make the analysis as up to date as possible. There were 94 papers, but only 39 were appropriate for review. The following themes were found from the review of resources; empathy as a feeling, skill, relationship and response, communicating empathy, patient outcomes, environmental influences and variables. From this, the defining new defining attributes of empathy were decided upon. These were empathy as a skill, empathy as a feeling, empathy as a communicative process, empathy in a relationship and empathy as a response. The Cases were then presented based on a nurse-patient relationship within a clinical setting. The antecedents of empathy are; patient distress, identification, intention of knowing, emotional stability, intellectual ability and time to care. The consequences of empathy are; the validation of the patient’s feelings, an action plan is put in place, positive patient outcomes and detachment. Government publications related to empathy, ‘standard text’ and empathy measuring tools are discussed within the empirical referents. Recommendations on how empathy can be implemented into practice are then discussed.